Interpreting the Reformation in Africa: Transformative hermeneutics of Manas Bethulezi in light of 500 years of the Reformation. Issue 2 (30th May 2019) - Mtata, Kenneth
Abstract: A cursory look at the various histories of religious renewal shows three interrelated aspects; there is an experience of injustice that is followed by the religious movement's new revitalization through the special encounter or reference to divine communication, and then an effort to reorganize the socio‐economic and political structures of society in light of the newly discovered religious vitality. This article observes in the phenomenology of religious renewal that cultural renewal and cultural distinctiveness tend to accompany religious renewal.